1989
DOI: 10.1152/ajpheart.1989.256.3.h867
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intracellular alkalinization on resting and agonist-induced vascular tone

Abstract: To evaluate the influence of intracellular alkalinization on basal and agonist-induced vascular tone, we studied the effect of NH4Cl on rat aorta. NH4Cl induced a gradually developing contraction in a dose-dependent manner. Although the contractile response to 20 mM NH4Cl was associated with a latent period (LP) of 23.4 +/- 2.8 min, intracellular pH (pHi) measurements in cultured rat aortic smooth muscle cells showed that NH4Cl-induced intracellular alkalinization was immediate and transient, returning to basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 0 publications
4
21
0
Order By: Relevance
“…On the other hand, NH« + slowly enters into the cell and releases H + , leading to a gradual normalization of pH,. 16 Thus, NH,Cl-induced attenua- tion of acetylcholine relaxation may follow pH, alteration with NH4CI treatment. Moreover, amiloride normalized the suppressive effect of the 10-minute treatment of NH4CI but not the 0-minute treatment, although nigericin inhibited NHiCl-induced attenuation irrespective of the treatment period.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, NH« + slowly enters into the cell and releases H + , leading to a gradual normalization of pH,. 16 Thus, NH,Cl-induced attenua- tion of acetylcholine relaxation may follow pH, alteration with NH4CI treatment. Moreover, amiloride normalized the suppressive effect of the 10-minute treatment of NH4CI but not the 0-minute treatment, although nigericin inhibited NHiCl-induced attenuation irrespective of the treatment period.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by the present finding that the effect of NH4CI disappeared in a time-dependent fashion ( Table 2). When NH4CI was added extracellularly, NH 3 rapidly moves into intracellular spaces and binds H + , resulting in intracellular alkalinization, in vascular smooth muscle 16 and endothelial 17 cells. On the other hand, NH« + slowly enters into the cell and releases H + , leading to a gradual normalization of pH,.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, two lines of evidence indicate that these two inhibitors block IRCM-induced vasodilatation via different mechanisms: (i) iodixanol-induced relaxation was unaffected by the presence of EIPA and (ii) combined incubation with both inhibitors synergistically attenuated iohexol-induced relaxation, whereas the effects of ouabain against iodixanol-induced vasodilatation were not enhanced by EIPA. Stimulation of Na' -H' exchange elevates intracellular pH ([pH]i), which mediates relaxation of rat aorta precontracted with PhE or K+ (Danthuluri & Deth, 1989) and in cardiac myocytes causes a fall in intracellular Ca2" concentration ([Ca2+]J) by 60% (Kim et al, 1987). Levitsky and Benevolensky (1986) showed that elevated [pH]i enhanced Ca2" sequestration by cardiac sarcoplasmic reticulum.…”
Section: Discussionmentioning
confidence: 99%